Lost Blurs: A Screenplay Exploring Child Neglect - Aloysius Reynaldo Danuega Hartanto; Ribut Basuki (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
This paper aims at exploring child neglect cases and to raise awareness about it. Child neglect is the failure to provide for the shelter, safety, supervision, and nutritional needs of the child. Child neglect is an underrated topic because it can be difficult to determine whether a parent is neglecting his/her child due to its unintentional nature. This paper explores what child neglect is, the possible effect of it such as disorganized attachment disorder, and ways to recover from said disorder. This paper uses the Attachment Theory by John Bowlby and the finding of the research is in the form of a screenplay. The screenplay uses tragicomedy as its genre, telling a story about a boy, Benny, who was neglected by his father as a child and now suffers from disorganized attachment disorder. Throughout his journey, he tries to recover from it by building trustful relationships and face his father about his neglected past.Keywords: child neglect, disorganized attachment disorder, screenplay, tragicomedy